2015
DOI: 10.1016/j.juro.2014.07.096
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes with Advancements in High Intensity Focused Ultrasound Devices for the Treatment of Localized Prostate Cancer

Abstract: Long-term followup of patients with high intensity focused ultrasound demonstrated improved clinical outcomes due to technical, imaging and technological advancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 21 publications
3
53
0
1
Order By: Relevance
“…Uchida and colleagues [15] have shown that successive improvements in technology of the HIFU device results in improvements in disease control in a total of 918 patients over a 13-yr period. The 10-yr overall and cancer-specific survival was 89.6% and 97.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Uchida and colleagues [15] have shown that successive improvements in technology of the HIFU device results in improvements in disease control in a total of 918 patients over a 13-yr period. The 10-yr overall and cancer-specific survival was 89.6% and 97.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA safety limit for diagnostic ultrasound use is to be within an MI of 1.9 (FDA, 2008). However, the FDA has approved of HIFU for the treatment of uterine fibroids (Tempany et al, 2003), pain palliation of metastatic bone cancer (Catane et al, 2007), and most recently prostate cancer (Crouzet et al, 2014; Uchida et al, 2014). Clinical trials for some neurological diseases, such as essential tremor disorder, are currently underway (Lipsman et al, 2013).…”
Section: Safety Of Focused Ultrasound and Microbubble Mediated Blomentioning
confidence: 99%
“…The risk after salvage cryotherapy is slightly higher at 10–11.7% (16,25). The incidence of urethral stenosis after HIFU is around 10% (1.8–40%) in the primary setting and 15-20% in salvage setting, mostly seen in the bladder neck and prostatic urethra (16,22,26,27). …”
Section: Introductionmentioning
confidence: 99%